2014
DOI: 10.2134/jeq2013.07.0286
|View full text |Cite
|
Sign up to set email alerts
|

Climate Change and Observed Climate Trends in the Fort Cobb Experimental Watershed

Abstract: Recurring droughts in the Southern Great Plains of the United States are stressing the landscape, increasing uncertainty and risk in agricultural production, and impeding optimal agronomic management of crop, pasture, and grazing systems. The distinct possibility that the severity of recent droughts may be related to a greenhouse-gas induced climate change introduces new challenges for water resources managers because the intensification of droughts could represent a permanent feature of the future climate. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 24 publications
5
12
0
Order By: Relevance
“…For agricultural and soil conservation applications, a supplemental downscaling step was necessary to express the projected monthly climate in terms of daily weather data at a particular location within the downscaled GCM grid-box. Synthetic weather generator SYNTOR (Garbrecht et al, 2014) was used to perform this supplemental downscaling (Fig. 2, middle).…”
Section: Climate Change Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…For agricultural and soil conservation applications, a supplemental downscaling step was necessary to express the projected monthly climate in terms of daily weather data at a particular location within the downscaled GCM grid-box. Synthetic weather generator SYNTOR (Garbrecht et al, 2014) was used to perform this supplemental downscaling (Fig. 2, middle).…”
Section: Climate Change Modelsmentioning
confidence: 99%
“…Stochastic weather generator SYNTOR (Garbrecht et al, 2014) was used in this study to downscale the monthly GCM climate predictions to daily weather outcomes at the location of interest within the GCM grid-cell.…”
Section: Downscaling Uncertaintymentioning
confidence: 99%
“…Second, the soil erosion distributions under both emission scenarios overlap significantly, indicating that both emission scenarios have similar impact on soil erosion. It is speculated that this is likely due to climate change in Oklahoma being primarily a change in min/max temperature (9%-34% increase, statistically significant; table 3), not a change in precipitation amount (6%-7% increase, not statistically significant; table 3; and Garbrecht et al, 2014a). Third, the combined uncertainty range of multiple emission scenarios (here RCP4.5 and RCP8.5) is always as large as or larger than that of an individual emission scenario.…”
Section: Climate Model Uncertaintymentioning
confidence: 99%
“…Temperatures are expected to continue to rise due to unabated releases of heat-trapping greenhouse gases (GHG) in the atmosphere (Dore, 2005;Tebaldi et al, 2006;NCADAC, 2009;AMS, 2013;IPCC, 2013). A warmer climate and more frequent and extreme rainfall events generally lead to a disproportional increase in surface runoff and soil erosion by water, thereby altering the extent of soil conservation efforts needed to stay within desirable soil erosion limits (SWCS, 2007;Izaurralde et al, 2011;Zhang et al, 2011;Dabney et al, 2012;Zhang, 2012;Walthall et al, 2013;Garbrecht et al, 2014a). Potential impacts of climate change on soil erosion by water must be estimated to establish the need for development of mitigating and adaptive strategies that maintain a competitive, sustainable, and environmentally responsible agricultural system under changing climatic conditions.…”
mentioning
confidence: 99%
“…The Intergovernmental Panel on Climate Change (IPCC) reported that global climate change was intensifying the hydrologic cycle (IPCC 2007) with projected precipitation and frequency of extremely wet seasons to increase over much of the United States (Christensen et al 2007). Temperatures will continue to rise in the near future (Dore 2005;Tebaldi et al 2006), and precipitation trends are uncertain and may increase or decrease for various locations and seasons (Hayhoe et al 2007;Diodato and Bellocchi 2009;Campbell et al 2011;Garbrecht et al 2014). Intensified precipitation and increased frequency of extreme events would likely result in more runoff, higher soil erosion rates, potentially severe gullying, and related off-site sedimentation problems (SWCS 2007; Zhang et al 2010;Zhang et al 2012;Dabney et al 2012a).…”
mentioning
confidence: 99%